Pemanfaatan Digital Marketing Melalui Aplikasi Facebook Dalam Meningkatkan Brand Awareness Pada Produk Karang Hias (Coral) Di PT. Dirga Mega Cipta Bekasi Jawa Barat - Elisa Putri; Ilham Ilham; Sulkifli Sulkifli (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The era of industrial revolution 4.0 has had a major impact on the digitalization process in all fields. Including the use of social media which has dramatically changed marketing trends in the world from conventional to digital. Business people are targeting increasing brand awareness by utilizing digital marketing. The aim of this research is to determine the influence of digital marketing variables in increasing brand awareness about coral products among users of the @coraledukasi account. This research uses a quantitative approach, data obtained from a questionnaire distribution with 37 respondents and then analyzed using multiple linear regression analysis with the help of the SPSS version 22 application. The results of this research show that digital marketing simultaneously has a significant influence on brand awareness and partially on the variables accessibility and informative has a significant effect while the interactivity variable has no significant effect.